2001
DOI: 10.1042/bj3590175
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of mutations in housefly (Musca domestica) acetylcholinesterase involved in insecticide resistance

Abstract: Acetylcholinesterase (AChE) insensitive to organophosphate and carbamate insecticides has been identified as a major resistance mechanism in numerous arthropod species. However, the associated genetic changes have been reported in the AChE genes from only three insect species; their role in conferring insecticide insensitivity has been confirmed, using functional expression, only for those in Drosophila melanogaster. The housefly, Musca domestica, was one of the first insects shown to have this mechanism; here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(43 citation statements)
references
References 33 publications
(51 reference statements)
3
37
0
1
Order By: Relevance
“…In the housefly Musca domestica and the Colorado potato beetle Leptinotarsa decemlineata, the cloned ace genes seem to be involved in resistance, as indicated by the identification of one or several mutations in strains with an insensitive AChE (Zhu et al 1996;Kozaki et al 2001;Walsh et al 2001). However, in several other arthropod species, the cloned ace gene codes for an AChE that is apparently not involved in resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the housefly Musca domestica and the Colorado potato beetle Leptinotarsa decemlineata, the cloned ace genes seem to be involved in resistance, as indicated by the identification of one or several mutations in strains with an insensitive AChE (Zhu et al 1996;Kozaki et al 2001;Walsh et al 2001). However, in several other arthropod species, the cloned ace gene codes for an AChE that is apparently not involved in resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It is established beyond doubt that resistance in D. melanogaster and M. domestica is caused by mutations at the ace-2 locus Walsh et al 2001). It has been shown for some years that, in Cx.…”
Section: (B) Insecticide Resistance and Ace Genesmentioning
confidence: 99%
“…The G353A mutation was also found in AChE from the fruit fly (G324A) (7), the house fly (G262A) (8), Lucilia cuprina (G303A) (11), and Plutella xylostella AChE1 (G324A) (12). Initial modeling of these mutations within the Drosophila structure revealed that G324A is located close to the active-site triad at the base of the gorge, with G324A likely to interact with gorge residues, which affects the orientation of the catalytic serine (ser-200 in Torpedo) and possibly plays a role in influencing inhibitor sensitivity (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Resistensi yang berkaitan dengan enzim dapat terjadi dengan terjadinya mutasi pada enzim yang dimaksud sehingga meningkatkan aktivitas katalitik enzim yang bersangkutan (Hemingway et al 2002;Hemingway et al 2004;Walsh et al 2001) dan/atau meningkatnya jumlah enzim yang diekspresikan (Field et al 1999;Fournier et al 1992). Dengan meningkatnya aktivitas total enzim yang bersangkutan, maka konversi senyawasenyawa toksik insektisida menjadi senyawa yang tidak bersifat toksik dapat berlangsung lebih efektif.…”
Section: Mekanisme Biokimia Resistensiunclassified